Tras asir el lenguaje: desarrollo de la lectura crítica de textos literarios narrativos breves en la educación superior - Saucedo Segami, Carmen (2022)
Literature as an artistic phenomenon is a proposal to create meaning and negotiate aesthetic values within a community. When this interaction occurs in the university environment, building up meaning is part of the academic discursive practices. Becoming familiar with these practices and successfully reproducing them requires specialized training. This article is based on the theory of critical reading, and presents a systematic and functional methodology to strategically read short narrative literary texts in an early-year college literature class. This competency-based approach privileges the collective construction of meaning and gives the student an active role in their learning. Therefore, it trains individuals capable of reading critically and appreciating an artistic product. We include a guide to commenting on short stories and a methodology for class discussion.